2022
DOI: 10.1016/j.cmi.2021.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Combined epidemiological and genomic analysis of nosocomial SARS-CoV-2 infection early in the pandemic and the role of unidentified cases in transmission

Abstract: The COVID-19 Genomics UK (COG-UK) consortium, Combined epidemiological and genomic analysis of nosocomial SARS-CoV-2 infection early in the pandemic and the role of unidentified cases in transmission, Clinical Microbiology and Infection,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
(14 reference statements)
2
25
0
Order By: Relevance
“…To support the generalisability of our findings, we included studies with implicit and explicit definitions of nosocomial COVID-19. Accordingly, we catalogued a wide spectrum of case definitions, including combined epidemiological and genomic viral sequencing (38). We controlled for this variation in case definitions within our sensitivity analyses, for instance using outcomes meeting consensus international criteria for definite nosocomial infection wherever available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support the generalisability of our findings, we included studies with implicit and explicit definitions of nosocomial COVID-19. Accordingly, we catalogued a wide spectrum of case definitions, including combined epidemiological and genomic viral sequencing (38). We controlled for this variation in case definitions within our sensitivity analyses, for instance using outcomes meeting consensus international criteria for definite nosocomial infection wherever available.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, a range of case definitions were employed to distinguish community-acquired and nosocomial COVID-19. A fixed interval between admission and diagnosis was employed in 14/21 (62%) ranging from >2 days (37) >14 days (12), supplemented by additional patient-level clinical data (40) and viral whole genome sequencing (38). Seven studies primarily employed epidemiological nosocomial definitions, for instance a history of close contact with positive cases [n=3 (27,31,39)], or the absence of symptoms on admission with subsequent positive test [n=2 (10,30)].…”
Section: Case Definitionsmentioning
confidence: 99%
“…Consequently, only 5 patients were inappropriately placed on a COVID-19 negative ward over the 2-weeks. All were moved within 10 hours following laboratory PCR results and no onward transmission was identified by either hospital contact tracing combined with reviewing genome sequence results of isolates from available probable and definite hospital-acquired cases, important given potential for cryptic linkage between wards [ 13 ]. In addition, only three genuine false-positive results were identified from 906 tests during the high prevalence period.…”
Section: Discussionmentioning
confidence: 99%
“…95% confidence intervals were determined using the Wilson/Brown binomial test. All clinical SARS-CoV-2 genome sequence reports in the caseof LFD false-negative patients and for any sequenced first-isolate taken >8 days post-admission (defined as a hospital-acquired case) between January 7 th and February 28th were reviewed that used difference of <= 1 SNP difference to define linkage [ 13 ]. During the continuation phase data on admission bed space, symptom onset, and assessing clinician’s impression were not collected.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing technologies can now be used for local outbreak investigation in near real-time, and this was implemented by some research centres for evaluation of nosocomial transmission from the early stages of the pandemic [2] . It has been demonstrated that sequencing can provide additional information on outbreak characteristics and transmission routes in comparison to traditional epidemiological investigation alone [2][3][4] . However, limited data are available on the feasibility of routine use of sequencing for infection prevention and control (IPC), or on its direct impact on IPC actions and nosocomial transmission rates.…”
Section: Introductionmentioning
confidence: 99%